2020
DOI: 10.1007/s10557-020-07038-1
|View full text |Cite
|
Sign up to set email alerts
|

Rationale, Design, and Baseline Characteristics of the BioProsthetic Valves with Atrial Fibrillation (BPV-AF) Study

Abstract: Purpose To date, clinical data on real-world treatment practices in Japanese patients with atrial fibrillation (AF) after bioprosthetic valve (BPV) replacement are needed. We conducted a large-scale, prospective, multicenter study to understand the actual usage of antithrombotic therapy and the incidence of thromboembolic and bleeding events in these patients, and to eliminate the clinical data gap between Japan and Western countries. Methods This was an observational study, in patients who had undergone BPV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
1
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 23 publications
0
13
1
4
Order By: Relevance
“…The clinical characteristics in our study were different from those reported in previous studies ( 6 , 7 , 10 , 11 ). Patients were younger in our study than those in previous studies.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…The clinical characteristics in our study were different from those reported in previous studies ( 6 , 7 , 10 , 11 ). Patients were younger in our study than those in previous studies.…”
Section: Discussioncontrasting
confidence: 99%
“…The related reasons might be as follows: first, the enrollment in the present study was based on the patients who underwent BVR at our hospital and discharged with AF diagnosis. The patients who developed AF after the BPV were not included, which was the enrollment criteria for the BPV-AF study ( 7 ), and these patients were generally older and had more comorbidities than patients in our study. Second, according to the Cardiovascular Surgery Outcomes 2019 published by Fuwai Hospital ( 19 ), which is the largest medical center for cardiovascular diseases in China, the proportion of the application of BPVs was only 20%, significantly lower than that in other countries.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prospective large-sample studies analyzing nationwide Japanese data are warranted. A large-scale prospective registry study (UMIN0 0 0 034485) in patients with AF with bioprosthetic valves is currently in progress [21] .…”
Section: Limitationsmentioning
confidence: 99%
“…A large-scale prospective study (UMIN000034485) in AF patients with bioprosthetic valves is currently in progress. 35 efficacy events without increasing safety outcomes by adding SAPT on anticoagulant therapy. Moreover, there is a possibility that the clinical backgrounds may be different between patients after bioprosthetic valve replacement and those with lone AF.…”
Section: Study Limitationsmentioning
confidence: 99%